2018
DOI: 10.1038/s41396-018-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Consistent changes in the taxonomic structure and functional attributes of bacterial communities during primary succession

Abstract: Ecologists have long studied primary succession, the changes that occur in biological communities after initial colonization of an environment. Most of this work has focused on succession in plant communities, laying the conceptual foundation for much of what we currently know about community assembly patterns over time. Because of their prevalence and importance in ecosystems, an increasing number of studies have focused on microbial community dynamics during succession. Here, we conducted a meta-analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 79 publications
11
84
0
2
Order By: Relevance
“…Moreover, multiple taxa should be considered in concert to achieve a holistic understanding of how belowground biodiversity changes during pedogenesis. Second, most studies reported to date have focused on changes in belowground biodiversity during initial stages of primary succession (i.e., years to centuries) (13,22), with few studies evaluating effects over much longer time scales (i.e., from centuries to thousands or millions of years) (13,15,16). The fate of belowground biodiversity is expected to differ between early and late stages of pedogenesis, because older ecosystems may enter a retrogressive phase (19,(23)(24)(25).…”
Section: Significancementioning
confidence: 99%
“…Moreover, multiple taxa should be considered in concert to achieve a holistic understanding of how belowground biodiversity changes during pedogenesis. Second, most studies reported to date have focused on changes in belowground biodiversity during initial stages of primary succession (i.e., years to centuries) (13,22), with few studies evaluating effects over much longer time scales (i.e., from centuries to thousands or millions of years) (13,15,16). The fate of belowground biodiversity is expected to differ between early and late stages of pedogenesis, because older ecosystems may enter a retrogressive phase (19,(23)(24)(25).…”
Section: Significancementioning
confidence: 99%
“…Trait‐based approaches also enable one to address macroecological questions by potentially reducing species‐specific context dependency and allowing for generalisation across communities and ecosystems (Hortal et al, ; Kunstler et al, ; McGill, Enquist, Weiher, & Westoby, ; Moretti et al, ; Statzner, Bis, Dolédec, & Usseglio‐Polatera, ; Suding et al, ). Trait‐based approaches are employed in many organism groups such as plants (Guittar, Goldberg, Klanderud, Telford, & Vandvik, ; Kergunteuil, Descombes, Glauser, Pellissier, & Rasmann, ), animals (Castro, Dolédec, & Callisto, ; Frimpong & Angermeier, ; Luck, Lavorel, Mcintyre, & Lumb, ; Poff et al, ), phytoplankton (Litchman & Klausmeier, ), and microorganisms (Allison, ; Guittar, Shade, & Litchman, ; Ortiz‐Álvarez, Fierer, Los Ríos, Casamayor, & Barberán, ). However, there is considerable disparity in the methodological advancements among different organism groups.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial community functional profiles are typically of much lower variance compared to their taxonomic profiles likely because of the large proportions of “core” or “housekeeping” functions [18–20]. In this study, we showed that this lack of variance in functional profiles between samples leads to a strong correlation between functional profiles from metagenome sequencing and those estimated from references with PICRUSt, even when the sample labels are randomly shuffled (Fig.…”
Section: Discussionmentioning
confidence: 68%